1961
DOI: 10.1126/science.133.3446.104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amino Acid Feedings in Schizophrenic Patients Treated with Iproniazid

Abstract: Large oral doses of individual amino acids were given three or four times daily for periods of 1 week to schizophrenic patients, some of whom were maintained on iproniazid. Marked alterations in behavior in some patients were associated with the administration of l-methionine and of l-tryptophan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1
5

Year Published

1963
1963
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(72 citation statements)
references
References 9 publications
1
65
1
5
Order By: Relevance
“…The first evidence for a role of DNA methylation in schizophrenia came from the observation that treatment with an S-adenosyl-methionine precursor L-methionine, actually intensifies a number of schizophrenic symptoms (Pollin et al, 1961). Given that S-adenosyl-methionine is the methyl donor for the DNA methylation reaction, this result suggests that hypermethylation of DNA may contribute to schizophrenia.…”
Section: Dna Methylation In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…The first evidence for a role of DNA methylation in schizophrenia came from the observation that treatment with an S-adenosyl-methionine precursor L-methionine, actually intensifies a number of schizophrenic symptoms (Pollin et al, 1961). Given that S-adenosyl-methionine is the methyl donor for the DNA methylation reaction, this result suggests that hypermethylation of DNA may contribute to schizophrenia.…”
Section: Dna Methylation In Schizophreniamentioning
confidence: 99%
“…A second psychiatric condition in which altered DNA methylation has long been implicated is schizophrenia (Pollin et al, 1961;Bredy et al, 2010). The first evidence for a role of DNA methylation in schizophrenia came from the observation that treatment with an S-adenosyl-methionine precursor L-methionine, actually intensifies a number of schizophrenic symptoms (Pollin et al, 1961).…”
Section: Dna Methylation In Schizophreniamentioning
confidence: 99%
“…These studies showed that treatment with high-daily doses of L-methionine resulted in exacerbation of schizophrenic symptoms. 9,10 In addition, as compared to controls the rate of whole body methylation was found to be decreased in patients with schizophrenia. 11,12 It was suggested that these findings might reflect an enzymatic defect or a failure of a control mechanism of the single-carbon cycle in schizophrenic patients.…”
Section: Introductionmentioning
confidence: 97%
“…Homocysteine may elicit DNA damage response in neurons that promotes apoptosis and hypersensitivity to excitotoxicity. An oral methionine load has classically been reported to exacerbate schizophrenia and is of course converted to homocysteine (104)(105)(106).…”
Section: Amino Acid Disturbances: Glycine Serine and Homocysteinementioning
confidence: 99%